Poincar´e Type Inequalities for Linear Differential Operators - Anastassiou, George A. (CUBO, A Mathematical Journal, 2008)
Various Lp form Poincar´e type inequalities [1], forward and reverse, are given for a Linear Differential Operator L, involving its related initial value problem solution y, Ly, the associated Green‘s function H and initial conditions at point x0 âˆˆ â„.